Rising Sun: Prioritized outcomes for suicide prevention in the Arctic - Collins, Pamela Y.; Delgado, Roberto A.; Apok, Charlene; Baez, Laura; Bjerregaard, Peter; Chatwood, Susan; Chipp, Cody; Crawford, Allison; Crosby, Alex; Dillard, Denise; Driscoll, David; Ericksen, Heidi; et al. (Psychiatric Services, 2018)
The official published article is available online at https://doi.org/10.1176/appi.ps.201700505. The Arctic Council, a collaborative forum among governments and Arctic communities, has highlighted the problem of suicide and potential solutions. The mental health initiative during the United States chairmanship, Reducing the Incidence of Suicide in Indigenous Groups: Strengths United Through Networks (RISING SUN), used a Delphi methodology complemented by face-to-face stakeholder discussions to identify outcomes to evaluate suicide prevention interventions. RISING SUN underscored that multilevel suicide prevention initiatives require mobilizing resources and enacting policies that promote the capacity for wellness, for example, by reducing adverse childhood experiences, increasing social equity, and mitigating the effects of colonization and poverty.